Methamphetamine ‘facts’: The production of a ‘destructive’ drug in Australian scientific texts - Thomson, N.; Moore, David (Routledge, 2014)
In this article, we analyse the ways in which methamphetamine, its use, and those who consume it are discursively produced in Australian scientific research, drawing on theoretical concepts from the field of science and technology studies. Our interest is in how specific realities of methamphetamine and its use come to be enacted as scientific ‘facts’ through particular devices and processes, and the political effects of these enactments for people who consume methamphetamine. A mapping exercise of the scientific literature on methamphetamine was undertaken in order to trace the textual enactments of methamphetamine in scientific discourse. We focus on three claims repeatedly made in this literature. They are (1) methamphetamine is associated with dependence, (2) methamphetamine is harmful and (3) crystalline methamphetamine (or ‘ice’) is more harmful than other forms of methamphetamine. Through focusing on these claims, we seek to underline the contingency of facts, making visible the contradictions and political choices involved in the haste to generate knowledge about this drug.